Evaluating the Developed Science Curriculum (Collins) for the first Basic-Grade from Teachers’ and Supervisors’ Perspectives in Ma’an Governates - Salah, Suhier Mahmoud; Jwaifell, Mustafa (Journal of Educational and Psychological Sciences, 2021)
The study aimed to evaluate the developed science curriculum (Collins) for the first basic grade, from the point of view of teachers and supervisors in Ma'an Governorate. The analytical approach was used to develop study tools, and the descriptive survey approach was used to evaluate the developed science curriculum (Collins) from teachers’ and supervisors’ perspectives. The curriculum evaluation tool, from the teachers’ and / supervisors’ perspectives, consisted of (62) items of the curriculum evaluation criteria distributed into six areas. The validity and reliability of the study tools were verified. The study community consisted of all science teachers and supervisors for the first grade in the directorates of education in Ma'an governorate, who were (3) male and female supervisors, and (131) male and female teachers. The results showed that the curriculum estimates from the teachers' and supervisors' point of view, with an average degree for each of the developed science curriculum for the first elementary grade, and that the ratings of the educational supervisors, in the evaluation score of the advanced science curriculum (Collins) for the first grade, are higher than that of the teachers ’evaluation in the areas: (educational outcomes, curriculum content, evaluation).Based on the findings of the study, it is recommended to: Conduct analytical studies of the developed science curriculum for the first elementary grade. And with follow-up and oversight from the supervision department to ensure that, the curriculum is implemented as planned, and the involvement of national curriculum experts in the curriculum development process to ensure its suitability to the philosophy of the Ministry of Education.
Keywords: Curriculum Development; Collins Curriculum; Science Curriculum; First Grade